Cohesion policy in the light of place-based innovation support: New approaches in multi-actors, decentralised regional settings with bottom-up strategies? - Thomas Stahlecker; Knut Koschatzky (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2010)
According to the Barca report and the OECD, the place-based development approach is a new paradigm of regional policy. It underlines the necessity to distribute policy design and implementation among different policy levels in order to tailor policy measures to the specific local conditions. Place-based initiatives inherit a strong bottom-up element in public governance. Taking the innovation orientation in European cohesion policy as a starting point, it is the objective of this paper to analyse whether the recent implementation of structural and cohesion policy shows indications for place-based policy designs and governance. Germany is used as a case study, because it can be expected that in federal systems multi-level and bottom-up policy structures are already strongly evident. The major question the paper seeks to answer is whether the recent experiences from German cohesion policy formulation and implementation allow to identify starting points for the future design of European cohesion policy.
urn:nbn:de:0011-n-1515736
Keywords: 330; place-based approach; cohesion policy; multi-level governance; innovation policy; Germany